The relationship between adolescent depressive symptomology and substance abuse - L.G. Blore; S. Schulze; A.C. Lessing (AOSIS, 2004)
The research aimed to investigate the phenomena of adolescent depressive symptomology, substance abuse and the relationship between the two phenomena in a South African context. The influence of moderator variables was also examined. Another objective was to determine risk factors for the before mentioned. This was done by using a questionnaire with a sample of 1298 conveniently selected adolescents in a South African high school. It was determined that adolescents become progressively unhappier from 13 to 17 years of age. Girls are more depressed than boys. This research also revealed that adolescent depressive symptomology is significantly and positively correlated with earlier age of onset of substance abuse as well as frequency of usage. There appear to be no gender differences in substance abuse but teenagers from different ethnic and language groups differ in their use of substances. Risk factors for depression and substance abuse included a conflict relationship with parents, the experience of major stressful events, dissatisfaction with school grades and friends' use of substances.